If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18x + -8 = 13x + -33 Reorder the terms: -8 + 18x = 13x + -33 Reorder the terms: -8 + 18x = -33 + 13x Solving -8 + 18x = -33 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. -8 + 18x + -13x = -33 + 13x + -13x Combine like terms: 18x + -13x = 5x -8 + 5x = -33 + 13x + -13x Combine like terms: 13x + -13x = 0 -8 + 5x = -33 + 0 -8 + 5x = -33 Add '8' to each side of the equation. -8 + 8 + 5x = -33 + 8 Combine like terms: -8 + 8 = 0 0 + 5x = -33 + 8 5x = -33 + 8 Combine like terms: -33 + 8 = -25 5x = -25 Divide each side by '5'. x = -5 Simplifying x = -5
| 2x-6+21=-3 | | -b-10=10+10+9b | | 4x-84=72-9x | | 4(2x+9)=-46+10 | | 2(x-3)-5(x-1)=4 | | -2x-5y=12forY | | b-10=10+10+9b | | 3(5x+6)-2(3-4x)=-11 | | 5z+14=7z-30 | | 4n^2-12n-320=0 | | x*x-100=0 | | 10-d=d-8 | | 340=x*490 | | 5(3t-4)-6=12t+4 | | -3r+6=r-6 | | 10-3y=6 | | 8u=7u+1 | | 18-13=1/2a=3/4a-5/8a | | 2z/7-2=7 | | 8y+4-6y=8+y+1 | | -8y-20=5y-20 | | -10q=-9q+6 | | Y=9+-0.5x | | 1/3(6n-9) | | -2(x-3)=x+24 | | 7xblank=84 | | 2(3y+5)=5(y+1) | | 36=I^2*9 | | 6x+-2(x+4)=12 | | 9-1(-1-3y)=4+y-(3-y) | | -2x-6=x+24 | | 4y+3y=2 |